The Effect of Safety Meeting-Based Health Education on Knowledge and Attitudes of HIV/AIDS Prevention Among Employees in Papua - Yani, Tri Ardayani (Journal of health research and technology, 2025)
The virus known as the Human Immunodeficiency Virus (HIV) attacks white blood cells, lowering immunity and leading to AIDS. The symptoms of HIV infection lead to a decline in human immunity, which can result in acquired immunodeficiency syndrome, or AIDS. Their ignorance of the fundamentals of how HIV/AIDS spreads to other people is the cause of many occurrences of the disease. Making an effort to educate people is one way to stop the spread of HIV/AIDS. Increased awareness of HIV/AIDS through education can promote behavioral changes and preventative measures. To combat and lower the number of HIV/AIDS cases, attitudes and behaviors toward prevention are essential. Pre-Experimental with the One Group is the research methodology employed in this study. Design method: Pre-Test Post-Test. Giving broad information on HIV/AIDS and how to prevent it through a safety meeting that uses PowerPoint is the study's independent variable. Knowledge of HIV/AIDS and attitudes toward HIV/AIDS prevention are the study's dependent variables. There were 113 participants in the study.53 individuals make up the sample size. utilizing a basic random sampling strategy for sampling. A validity test using the same respondent characteristics was carried out at PT Y. A questionnaire was the tool utilized. bivariate Shapiro-Wilk analysis and univariate frequency distribution. From March to July 2024, this study was carried out at PT X in Tembagapura District, Mimika Regency, Central Papua. With a P value of 0.000 <alpha 0.05, there is a difference in HIV/AIDS preventive knowledge before and after health education through safety meetings. A P value of 0.000 <alpha 0.05 indicates that attitudes about HIV/AIDS prevention are influenced both before and after health education through safety meetings.